Production and profitability of sorghum (Sorghum bicolor L. Moench) based intercropping system under rainfed condition - SINGH, RAGHVENDRA; KUMAR, MUNISH; KUMAR, SARVESH; YADAV, A.S.; KUMAR, PRADEEP (Journal of Soil and Water Conservation, 2022)
A field experiment was conducted to evaluate sorghum based intercropping systems with moongbean, urdbean and soybean as intercrops in rainfed conditions at Chandra Shekhar Azad University of Agriculture & Technology, Kanpur Nagar, U.P. during Kharif season, 2014-15 with 10 treatment viz.T1- sorghum sole (45 cm) - apart, T2-moongbean sole (45 cm )- apart, T3-urdbean sole (45 cm) apart, T4- soybean sole (45 cm) - apart,T5-sorghum + moongbean (2:1), T6-sorghum + urdbean (2:1), T7-sorghum + soybean (2:1), T8: Sorghum + soybean (3:1), T9 -soybean + moongbean (3:1), T10-sorghum + urdbean (3:1)in randomization block design with three replication. The results of experimental revealed that sorghum + soybean paired with 3:1 row ratio gave significantly highest production (23.92 q ha-1) and earned maximum net return of Rs. 29,547 ha-1.